comparison of the effects of 2 doses of soy protein or casein on serum lipids, serum lipoproteins, and plasma total homocysteine in hypercholesterolemic subjects - Tonstad, Serena; Smerud, Knut; Høie, Lars (The American journal of clinical nutrition, 2002)
Background: Studies have shown that soy protein reduces some atherogenic lipid and lipoprotein concentrations, although lipoprotein(a) concentrations may be increased. The dose response of soy protein has not been established; neither has its effect on plasma total homocysteine. Objective: Our objective was to evaluate the effect of 2 doses of soy protein on lipid, lipoprotein, and homocysteine concentrations. Design: Four to 24 wk after being instructed to consume a lipid-lowering diet, 130 men and women with LDL-cholesterol concentrations ≥ 4 mmol/L were studied during a parallel group trial in which 4 interventions were assigned randomly. Thirty grams isolated soy protein (ISP) and 10 g cotyledon fiber or 50 g ISP and 16.6 g cotyledon fiber or equivalent doses of casein and cellulose were consumed daily as a beverage for 16 wk. Results: When the 2 groups who consumed ISP were compared with the 2 groups who consumed casein, the differences in the net changes from baseline to week 16 in the concentrations of LDL cholesterol and plasma total homocysteine were −0.26 mmol/L (95% CI: −0.43, −0.09 mmol/L; P = 0.01) and −0.8 μmol/L (−1.4, −0.2 μmol/L; P = 0.005), respectively. The effect of the ISP dose was not significant. There were no significant differences between the 2 ISP and the 2 casein groups in changes in lipoprotein(a), HDL-cholesterol, or triacylglycerol concentrations. Conclusions: Adding 30–50 g soy protein/d to a lipid-lowering diet significantly reduced LDL-cholesterol concentrations without increasing lipoprotein(a) concentrations. Plasma total homocysteine concentrations also decreased, suggesting a novel, possibly antiatherosclerotic effect.